Electrochemical Deposition Enables Freestanding CoNi Layered Double Hydroxide/MnOX Electrode with Enhanced Electrochemical Properties for Asymmetric Supercapacitors. Issue 11 (22nd August 2019) - Tian, Songlin; Zhao, Cuimei; Nie, Ping; Wang, Hairui; Xue, Xiangxin; Lin, Li; Chang, Limin
Abstract : A carbon fiber paper (CFP)‐supported CoNi layered double hydroxide (LDH)/MnO X or MnO X nanomaterial is prepared by a simple and effective two‐step electrochemical deposition process. The binder‐free CoNi LDH/MnO X /CFP exhibits enhanced electrochemical properties than that of MnO X /CFP, with a maximum capacitance of 1460 F g −1 at 1 A g −1, and an excellent capacitance retention of 87% at 4 A g −1 . Notably, the CoNi LDH/MnO X composite exhibits a remarkable cycling stability with 82% capacitance retention over 20 000 cycles even at a high current density of 32 A g −1 . The outstanding electrochemical performance of the CoNi LDH/MnO X /CFP can contribute to the synergistic effects of the freestanding electrode with improved electrical conductivity, electrochemical activity, and material utilization than pure MnO X . Furthermore, an asymmetric supercapacitor (ASC) fabricated with a CoNi LDH/MnO X /CFP positive electrode and active carbon (AC)/CFP negative electrode displays a high energy density of 28.1 Wh kg −1 at a power density of 400 W kg −1 . These encouraging results indicate that the low‐cost CoNi LDH/MnO X /CFP composite shows great potential for high‐performance energy storage applications. Abstract : A facile method for the preparation of a binder‐free CoNi layered double hydroxide (LDH)/MnO x /carbon fiber paper (CFP) electrode is reported. The electrode shows excellent capacitive performance for asymmetric supercapacitors (ASCs).